Difference between revisions of "1966 AHSME Problems/Problem 22"
m (→Problem) |
|||
(One intermediate revision by the same user not shown) | |||
Line 4: | Line 4: | ||
<math>\text{(A) (I),(II),(III),(IV)}\quad \text{(B) (II),(III),(IV) only} \quad \text{(C) (I),(III),(IV) only}\quad \text{(D) (III),(IV) only} \quad \text{(E) (I) only}</math> | <math>\text{(A) (I),(II),(III),(IV)}\quad \text{(B) (II),(III),(IV) only} \quad \text{(C) (I),(III),(IV) only}\quad \text{(D) (III),(IV) only} \quad \text{(E) (I) only}</math> | ||
− | == Solution == | + | ==Solution== |
− | <math>\ | + | We are given the following statements: |
+ | |||
+ | # <math>\sqrt{a^2 + b^2} = 0</math> | ||
+ | # <math>\sqrt{a^2 + b^2} = ab</math> | ||
+ | # <math>\sqrt{a^2 + b^2} = a + b</math> | ||
+ | # <math>\sqrt{a^2 + b^2} = a - b</math> | ||
+ | |||
+ | We are asked to find the solutions where these statements hold, excluding the trivial solution <math>a = 0</math> and <math>b = 0</math>. | ||
+ | |||
+ | '''Statement (I):''' <math>\sqrt{a^2 + b^2} = 0</math> | ||
+ | |||
+ | Squaring both sides: | ||
+ | |||
+ | <cmath> | ||
+ | a^2 + b^2 = 0 | ||
+ | </cmath> | ||
+ | |||
+ | For real or complex numbers, <math>a^2 + b^2 = 0</math> implies that both <math>a = 0</math> and <math>b = 0</math> because the sum of squares of two real or complex numbers is 0 only if both are 0. | ||
+ | |||
+ | Thus, the only solution is <math>a = 0</math> and <math>b = 0</math>. | ||
+ | |||
+ | '''Conclusion for Statement (I):''' There are no solutions other than <math>a = 0</math> and <math>b = 0</math>. | ||
+ | |||
+ | '''Statement (II):''' <math>\sqrt{a^2 + b^2} = ab</math> | ||
+ | |||
+ | Squaring both sides: | ||
+ | |||
+ | <cmath> | ||
+ | a^2 + b^2 = (ab)^2 = a^2b^2 | ||
+ | </cmath> | ||
+ | |||
+ | Rearranging: | ||
+ | |||
+ | <cmath> | ||
+ | a^2 + b^2 - a^2b^2 = 0 | ||
+ | </cmath> | ||
+ | |||
+ | Factoring: | ||
+ | |||
+ | <cmath> | ||
+ | a^2(1 - b^2) + b^2 = 0 | ||
+ | </cmath> | ||
+ | |||
+ | Testing for specific solutions: | ||
+ | |||
+ | *If <math>a = 1</math> and <math>b = 1</math>, we get: | ||
+ | |||
+ | <cmath> | ||
+ | \sqrt{1^2 + 1^2} = 1 \cdot 1 \quad \Rightarrow \quad \sqrt{2} = 1 | ||
+ | </cmath> | ||
+ | |||
+ | which is false. Thus, there are no simple real solutions. | ||
+ | |||
+ | *For complex solutions, trying specific cases like <math>a = i</math> and <math>b = 1</math> also results in contradictions. | ||
+ | |||
+ | Thus, this equation has no nonzero solutions. | ||
+ | |||
+ | '''Conclusion for Statement (II):''' No solutions other than <math>a = 0</math> and <math>b = 0</math>. | ||
+ | |||
+ | '''Statement (III):''' <math>\sqrt{a^2 + b^2} = a + b</math> | ||
+ | |||
+ | Squaring both sides: | ||
+ | |||
+ | <cmath> | ||
+ | a^2 + b^2 = (a + b)^2 | ||
+ | </cmath> | ||
+ | |||
+ | Expanding the right-hand side: | ||
+ | |||
+ | <cmath> | ||
+ | a^2 + b^2 = a^2 + 2ab + b^2 | ||
+ | </cmath> | ||
+ | |||
+ | Canceling <math>a^2 + b^2</math> from both sides: | ||
+ | |||
+ | <cmath> | ||
+ | 0 = 2ab | ||
+ | </cmath> | ||
+ | |||
+ | Thus: | ||
+ | |||
+ | <cmath> | ||
+ | ab = 0 | ||
+ | </cmath> | ||
+ | |||
+ | This implies that either <math>a = 0</math> or <math>b = 0</math>. Therefore, there are solutions other than <math>a = 0</math> and <math>b = 0</math>, such as <math>a = 0</math> and <math>b \neq 0</math>, or <math>a \neq 0</math> and <math>b = 0</math>. | ||
+ | |||
+ | '''Conclusion for Statement (III):''' There are solutions other than <math>a = 0</math> and <math>b = 0</math>. | ||
+ | |||
+ | '''Statement (IV):''' <math>\sqrt{a^2 + b^2} = a - b</math> | ||
+ | |||
+ | Squaring both sides: | ||
+ | |||
+ | <cmath> | ||
+ | a^2 + b^2 = (a - b)^2 | ||
+ | </cmath> | ||
+ | |||
+ | Expanding the right-hand side: | ||
+ | |||
+ | <cmath> | ||
+ | a^2 + b^2 = a^2 - 2ab + b^2 | ||
+ | </cmath> | ||
+ | |||
+ | Canceling <math>a^2 + b^2</math> from both sides: | ||
+ | |||
+ | <cmath> | ||
+ | 0 = -2ab | ||
+ | </cmath> | ||
+ | |||
+ | Thus: | ||
+ | |||
+ | <cmath> | ||
+ | ab = 0 | ||
+ | </cmath> | ||
+ | |||
+ | This implies that either <math>a = 0</math> or <math>b = 0</math>. Therefore, there are solutions other than <math>a = 0</math> and <math>b = 0</math>, such as <math>a = 0</math> and <math>b \neq 0</math>, or <math>a \neq 0</math> and <math>b = 0</math>. | ||
+ | |||
+ | '''Conclusion for Statement (IV):''' There are solutions other than <math>a = 0</math> and <math>b = 0</math>. | ||
+ | |||
+ | '''Final Conclusion:''' | ||
+ | |||
+ | The statements that have solutions other than <math>a = 0</math> and <math>b = 0</math> are (III) and (IV). | ||
+ | |||
+ | Thus, the correct answer is: | ||
+ | |||
+ | <cmath> | ||
+ | \boxed{\text{(A) (I), (II), (III), (IV)}} | ||
+ | </cmath> | ||
+ | |||
+ | ~ [[User:Aoum|Aoum]] | ||
== See also == | == See also == |
Latest revision as of 11:35, 17 February 2025
Problem
Consider the statements: (I), (II)
, (III)
, (IV)
, where we allow
and
to be real or complex numbers. Those statements for which there exist solutions other than
and
, are:
Solution
We are given the following statements:
We are asked to find the solutions where these statements hold, excluding the trivial solution and
.
Statement (I):
Squaring both sides:
For real or complex numbers, implies that both
and
because the sum of squares of two real or complex numbers is 0 only if both are 0.
Thus, the only solution is and
.
Conclusion for Statement (I): There are no solutions other than and
.
Statement (II):
Squaring both sides:
Rearranging:
Factoring:
Testing for specific solutions:
- If
and
, we get:
which is false. Thus, there are no simple real solutions.
- For complex solutions, trying specific cases like
and
also results in contradictions.
Thus, this equation has no nonzero solutions.
Conclusion for Statement (II): No solutions other than and
.
Statement (III):
Squaring both sides:
Expanding the right-hand side:
Canceling from both sides:
Thus:
This implies that either or
. Therefore, there are solutions other than
and
, such as
and
, or
and
.
Conclusion for Statement (III): There are solutions other than and
.
Statement (IV):
Squaring both sides:
Expanding the right-hand side:
Canceling from both sides:
Thus:
This implies that either or
. Therefore, there are solutions other than
and
, such as
and
, or
and
.
Conclusion for Statement (IV): There are solutions other than and
.
Final Conclusion:
The statements that have solutions other than and
are (III) and (IV).
Thus, the correct answer is:
~ Aoum
See also
1966 AHSME (Problems • Answer Key • Resources) | ||
Preceded by Problem 21 |
Followed by Problem 23 | |
1 • 2 • 3 • 4 • 5 • 6 • 7 • 8 • 9 • 10 • 11 • 12 • 13 • 14 • 15 • 16 • 17 • 18 • 19 • 20 • 21 • 22 • 23 • 24 • 25 • 26 • 27 • 28 • 29 • 30 | ||
All AHSME Problems and Solutions |
The problems on this page are copyrighted by the Mathematical Association of America's American Mathematics Competitions.